(untitled) (Nigerian Journal of Technology, 2014)
This work presents an alternative approach to the computation of the optimum reservations to be made in a GSM network for handover call requests. Prioritizing handover calls in a cellular network such as the GSM is necessary so as to guarantee seamless connection. Successful handover enhances the quality of service (QoS) of a network as the later is directly dependent on call continuity. In a previous analysis, the expression for the optimum reservations to be made was determined using the Gaussian Elimination method which had limitations because the power series used only considered the second order. Also, the set of equations to be solved was reduced to three thereby giving a result that does not quite represent the general system. In this work, the logarithmic approach is adopted which captures the total system capacity under test. A more reliable function for the determination of optimum reservations required in a system is thus derived. This new approach is also compared with that obtained using the Gaussian Elimination method.